Sustained disease control with aflibercept 8 mg: A turning point in the management of exudative retinal disease: Expert consenus (Ukrainian Journal of Ophthalmology, 2026)
Leading Ukrainian retinal disease specialists participated in the Advisory Board meeting held in Kyiv in late September 2025. The meeting aimed to determine the optimal approaches to using aflibercept 8 mg in Ukraine for sustained control of, and best possible treatment outcomes for patients with, exudative retinal disease. This paper contains all the key recommendations for which all the participants achieved consensus after discussion.